PERBEDAAN KINERJA REKSA DANA KONVENSIONAL DAN SYARIAH - Margaretha, Farah; ., Lyberisa (Manajemen Bisnis Kompetensi, 2014)
ABSTRACTÃ‚Â This purpose of this study is to know performance from unit trust that is syariah and conventional fund in Indonesia be based on rate of return and Treynor Index. As well as to know rate of risk based on selectivity and market timing. This research data obtained from 16 syariah fund and 23 conventional fund coming from three type unit trust that is, equity fund, fixed income fund, and mixed fund enlisted in BAPEPAM that were active during the research period since year 2006 until 2010. The analysis method which used in this study is normality test (Kolmogorov Smirnov) and Mann Whitney test. the Result of this study indicates that in general, performance of conventional and syariah unit trust has significan differences base to rate of return and Treynor Index. And rate of risk base to selectivity is significan differences, but base to market timing is no differences.Ã‚Â Keywords: UnitsTrust Performance, Rate of Risk, Units TrustÃ‚Â